THE INFLUENCE OF PERCEIVED PRICE, BRAND RECOGNITION AND CONSUMER ATTITUDE ON PURCHASE INTENTION OF PRIVATE LABEL PRODUCT AT ALFAMIDI MANADO - Vincensius, Resilooy Marcho; Pangemanan, Sifrid S.; Pandowo, Merinda . (Universitas Sam Ratulangi, 2017)
Abstract: The growth of the retail business provides various benefits to consumers to shop, but indirectly will result in consumers' perceptions in the shop. Marketing is defined as a process in society where the structure of demand for economic goods and services is anticipated or enlarged and satisfied through the conception, promotion, exchange and physical distribution of such goods and services. Therefore, a business needs to take seriously the management of goods or services offered to consumers. The purpose of this study is to determine whether there is influence of perceived prices, brand recognition and consumer attitudes toward the intention to buy private label products in Alfamidi Manado. The method used is multiple linear regressions with the number of samples in this study as many as 60 respondents as Alfamidi consumers, especially in retailers Alfamidi Citraland Winangun Manado. The results of this study indicate that the perceived price, brand recognition and consumer attitudes have affect on the purchase intention of private label products. The perceived price does not affect the purchase intention of private label products. Brand recognition has a positive and significant impact on purchase intention of private label products. Consumer attitudes have no effect on purchasing intention of private label product products.Keywords: marketing, purchase intention, perceived price, brand recognition, consumer attitude.